2017
DOI: 10.1017/s0029665116002986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent fasting on glucose and lipid metabolism

Abstract: Two intermittent fasting variants, intermittent energy restriction (IER) and time-restricted feeding (TRF), have received considerable interest as strategies for weight-management and/or improving metabolic health. With these strategies, the pattern of energy restriction and/or timing of food intake are altered so that individuals undergo frequently repeated periods of fasting. This review provides a commentary on the rodent and human literature, specifically focusing on the effects of IER and TRF on glucose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 55 publications
3
99
0
8
Order By: Relevance
“…174 Common fasting practices include the 5:2 plan (feed for 5 days and restrict calories to <70% for 2 days each week), alternate day fasting, and restricting eating to a 12-hour window each day. 175 However, few studies have examined the metabolic effects of fasting in humans; therefore, no recommendations regarding WD and fasting can be made with confidence at this time.…”
Section: Multifaceted Treatment Approachmentioning
confidence: 99%
“…174 Common fasting practices include the 5:2 plan (feed for 5 days and restrict calories to <70% for 2 days each week), alternate day fasting, and restricting eating to a 12-hour window each day. 175 However, few studies have examined the metabolic effects of fasting in humans; therefore, no recommendations regarding WD and fasting can be made with confidence at this time.…”
Section: Multifaceted Treatment Approachmentioning
confidence: 99%
“…The degree of caloric restriction may vary from partial to complete restriction. The schedule may involve restriction for several hours a day, alternate days or several days per week . A systematic review, but without meta‐analysis, of studies comparing intermittent fasting with daily energy restriction reported the same degree of weight loss between the two treatment options in nine out of 12 studies (75%).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the interest surrounding intermittent energy restriction (IER) as a potential strategy to improve compliance to energy-restricted diets has increased [3] although findings from a recent systematic review comparing IER to CER demonstrate equivalence [4]. Nonetheless, studies conducted demonstrate that IER is an effective strategy for weight loss and improving cardiometabolic health markers such as fasting insulin, lipids and blood pressure when delivered in controlled settings [5], whilst weight maintenance rates have been shown to be comparable to CER [6].…”
Section: Introductionmentioning
confidence: 99%